[Retracted Article] : Strengthen the production cost management of rice planting, the Ontai Rice Seed Center Community Enterprise in Sankamphaeng district, Chiang Mai [Area Based Development Research Journal, (2016), 8(3), 102-117] (in Thai) - Pongklang, Pikul (Area Based Development Research Journal, 2020)
Journal of Area-Based Development Research Retraction Notice The journal hereby retracts the article entitled “Strengthening Cost Management in Rice Production: The Case of the Community Enterprise Seed Center, On Tai Subdistrict, San Kamphaeng District, Chiang Mai Province.” due to the following findings. 1. The authors republished research results using the same dataset from a single research project in three separate journal issues. 2. Plagiarism was detected in the abstract, text passages, and several paragraphs across all three publications.